2013
DOI: 10.1038/ncomms2960
|View full text |Cite
|
Sign up to set email alerts
|

Capture and conversion of CO2 at ambient conditions by a conjugated microporous polymer

Abstract: Conjugated microporous polymers are a new class of porous materials with an extended π-conjugation in an amorphous organic framework. Owing to the wide-ranging flexibility in the choice and design of components and the available control of pore parameters, these polymers can be tailored for use in various applications, such as gas storage, electronics and catalysis. Here we report a class of cobalt/aluminium-coordinated conjugated microporous polymers that exhibit outstanding CO2 capture and conversion perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
398
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 700 publications
(411 citation statements)
references
References 34 publications
10
398
1
2
Order By: Relevance
“…19,20 Compared with other inorganic or inorganic-organic hybrid porous materials, CMPs have intrinsic advantages such as a high degree of p-conjunction, homogeneous microporous structure, ultrahigh specic surface area, diversity and exibility in the molecular design. Because of their unique features, CMPs have shown great potential in gas absorption, 21,22 gas separation, 23,24 heterogeneous catalysis 25,26 and so on. However, there have been only a few reports of CMPs applied for Li or Na storage.…”
mentioning
confidence: 99%
“…19,20 Compared with other inorganic or inorganic-organic hybrid porous materials, CMPs have intrinsic advantages such as a high degree of p-conjunction, homogeneous microporous structure, ultrahigh specic surface area, diversity and exibility in the molecular design. Because of their unique features, CMPs have shown great potential in gas absorption, 21,22 gas separation, 23,24 heterogeneous catalysis 25,26 and so on. However, there have been only a few reports of CMPs applied for Li or Na storage.…”
mentioning
confidence: 99%
“…Nevertheless, both high yields for cyclohexane oxide were obtained catalyzed by Mn-CTF (97%) and Ru-CTF (99%) after 24h (Entry 5 and 10). The high catalytic activity can be attributed to the enrichment of O 2 concentrations near the catalytic center located in the pore structures of Mn/Ru-CTF [16]. …”
Section: B the Catalytic Performance Of The Mn-ctf And Ru-ctfmentioning
confidence: 99%
“…However, no studies involving the use of their carbides as anode material for LIBs have been reported to date. In a continuation of our previous studies on CMP materials, [24,[33][34][35] herein we describe a strategy for the synthesis of porous hard carbons (PHC) by means of a simple one-step thermolysis of CMP precursors. The CMPderived PHC shows not only the desired porous structure and large SSA, but also exhibits a highly reversible specific capacity, large rate performance, and long cycling life, which make them the promising candidates as anode materials for high performance LIBs.…”
mentioning
confidence: 99%